Analisa Sifat Mekanik pada Komposit 86 Al 1020 – 12 Fly Ash – 2 Mg yang Dibuat dengan Proses Direct Melt Oxidation (DIMOX) - Qomarul Hadi; Ahmad Sumadi (Jurnal Rekayasa Mesin, 2021)
This study aims to analyze the mechanical properties of composite with a composition of 86% aluminum 1020, 12% fly ash and 2% magnesium, the three composite materials are combined in a furnace with the Direct Melt Oxidation method, after the melting process with a temperature of 900oC and the holding time varying 4 hours , 5 hours and 6 hours. Later, the Brinell hardness tester, at K4 the average value of BHN was 49.00816 kgf / mm, K5 the average value of BHN was 51.80066 kgf / mm and K6 the average value of BHN was 56.64983 kgf / mm. In the observation of Scaning Electron Microscope K6 specimens that have the best pores, changes in the microstructure of these composites are increasingly visible on the 5000x magnification observation. This is due to the holding time which helps the infiltration process in the interface reaction between the liquid and solid phases, and the user of this holding time is due to the metal's wetting ability and the slow and time-consuming infiltration process. to get a more even mixture.